A meaningful exploration of ofatumumab in refractory NMOSD: a case report - Zhan, Yibo; Zhao, Min; Li, Xiaojun; Ouyang, Huiying; Du, Chenghao; Chen, Guixian; Lou, Zhenzhen; Chen, Haoxuan; Zhao, Yuanqi; Xu, Haoyou (Frontiers in Immunology, 2023)
Objective To report the case of a patient with refractory neuromyelitis optica spectrum disorder (NMOSD), who, despite showing poor response or intolerance to multiple immunosuppressants, was successfully treated with Ofatumumab. Case presentation A 42-year-old female was diagnosed with NMOSD in the first episode of the disease. Despite treatment with intravenous methylprednisolone, immunoglobulin, rituximab and immunoadsorption, together with oral steroids, azathioprine, mycophenolate mofetil and tacrolimus, she underwent various adverse events, such as abnormal liver function, repeated infections, fever, rashes, hemorrhagic shock, etc., and experienced five relapses over the ensuing four years. Finally, clinicians decided to initiate Ofatumumab to control the disease. The patient received 9 doses of Ofatumumab over the next 10 months at customized intervals. Her symptoms were stable and there was no recurrence or any adverse events. Conclusion Ofatumumab might serve as an effective and safe alternative for NMOSD patients who are resistant to other current immunotherapies.